User-Friendly Smart Security System using ESP32 in Rental Rooms - Saumat, Murphy T.; Codate, Crianne Herc C.; Dayoc, Rey P. (Southeast Asian Journal of Science and Technology, 2023)
Face-to-face classes have compelled students to reside in temporary shelters, especially those who study far from home. Being in a new setting with unfamiliar individuals, students become more susceptible to theft, lacking any means to safeguard the privacy of their possessions. Technological advancement brought forth an era of automation where everything runs automatically without the need for human intervention. With knowledge of these advancements, the researchers made use of such technology in a security system. This paper developed a smart security system that can be applied in rental rooms, dormitories, or any establishment that caters to different individuals living in one room. The paper has five stages in gathering necessary data: room inspection, locating the optimal placement of sensors, wireless node system, system test, and data analysis. This data is used to determine the effectiveness of the smart security system. The study shows that smart security system response time is controlled by signal strength, not distance. The smart security system’s performance, efficiency, and efficacy depend on the user’s smartphone signal strength. The researchers concluded that the smart security system safeguards user assets, and the alarm alerts personnel without user intervention.